Is herding a safe haven for investment?. Issue 2 (19th January 2021) - Chen, Yi-Chang; Kuo, Shih-Ming; Yang, Yu-Wen
ABSTRACT: This paper investigates whether herd behaviour followed by fad can be regarded as a safe haven for investment. We found that investors have anticipatory herd behaviour towards the Apple fad. Herding creates a safe zone and is adopted as a means to reduce the risk of irrational behaviour, especially for companies with poor profitability. On the whole, herding may lead to positive market returns and can be used as a short-term safe haven under uncertainty.